REQUEST FOR COMPRESSION OF SOME INNOVATIVE MATERIALS - Constanța RADULESCU; Nicoleta-Maria MIHUȚ; Cristina IONICI; Minodora PASĂRE; Simona Ioana ZAMFIR (Fiabilitate şi Durabilitate)
Modern society seeks to capitalize waste on construction and demolition through various technologies. In this sense, a research topic can refer to the response of innovative materials to the classic compression stress, analyzing the values of tensile strength by types of material. In this work we used new materials from construction waste with different compounds, ceramic wall and floor tiles, brick and cement.